Wade and the scorpion's claw - Abbott, Tony, 1952- (Abbott, Tony, 1952- Copernicus archives, 2014)
"In this first in a series of ... [companion] novellas [to] the Copernicus legacy series, Wade travels to Hawaii and San Francisco in a race to find one of the twelve ancient relics"--